First total synthesis of seimatopolide B - Nookaraju, U.; Harbindu, Anand; Bhise, Ankushkumar D.; Sharma, Brijesh M.; Kumar, Pradeep (RSC Advances, 2012)
The first enantioselective total synthesis of seimatopolide B has been achieved, using ring-closing metathesis and DCC (N,N'-dicyclohexylcarbodiimide) coupling as key steps. The stereogenic centres were generated by means of iterative hydrolytic kinetic resolution (HKR) of racemic epoxides.

Asymmetric routes to pentadec-1-en-4-ol: application to the syntheses of aculeatins F and epi-F, (R)- and (S)-5-hexadecanolide and a formal synthesis of solenopsin - Harbindu, Anand; Sharma, Brijesh M.; Kumar, Pradeep (Tetrahedron-Asymmetry, 2013)
A short and simple route to the synthesis of pentadec-1-en-4-ol, an important synthetic building block for the aculeatins F and epi-F, insect pheromone 5-hexadecanolide, solenopsin and various other natural products has been developed via proline-catalyzed alpha-aminoxylation of an aldehyde and hydrolytic kinetic resolution of a terminal epoxide. While the synthesis of aculeatins F and epi-F has been accomplished using a FIFA promoted oxidative spirocyclization/dithiane deprotection reaction sequence and linchpin coupling as key steps, the synthesis of hexadecanolide and a formal synthesis of solenopsin was performed using ring-closing metathesis (RCM) as key step. (C) 2013 Elsevier Ltd. All rights reserved.

Enantioselective modular total synthesis of macrolides Sch725674 and C-4-epi-Sch725674 - Sharma, Brijesh M.; Gontala, Arjun; Kumar, Pradeep (European Journal of Organic Chemistry, 2016)
The convergent total synthesis of Sch725674 has been accomplished by starting from (R)-1,2-epoxyheptane and assembling five modules in a highly stereoselective manner to give the final product in 6.6% overall yield. The same strategy was extended to the synthesis of its C-4 epimer. Key reactions of the synthetic pathway include a Jacobsen hydrolytic kinetic resolution of an epoxide followed by its regioselective opening through a Yamaguchi-Hirao alkynylation, and ring-closing metathesis reaction to furnish the unique 14-membered ring macrolactone. In addition, the influence of protecting groups on the efficiency of the ring-closing metathesis (RCM) macrocyclization has been studied to maximize its yields.
Keywords: Asymmetric synthesis; Hydrolytic kinetic resolution; Macrocycles; Metathesis; Natural products

Tf2NH-catalyzed 1,6-conjugate addition of vinyl azides with p-quinone methides: a mild and efficient method for the synthesis of β-bis-arylamides - Rathod, Jayant; Sharma, Brijesh M.; Mali, Pramod S.; Kumar, Pradeep (Synthesis, 2017)
Tf2NH-catalyzed tandem 1,6-conjugate addition/Schmidt type rearrangement using vinyl azides and p-quinone methides to access a variety of β-bis-arylated amides is reported. The method is quick, efficient, mild, and high yielding with broad substrate scope.

Transition metal catalysis-a unique road map in the stereoselective synthesis of 1,3-polyols - Kumar, Pradeep; Tripathi, Divya; Sharma, Brijesh M.; Dwivedi, Namrata (Organic & Biomolecular Chemistry, 2017)
The present review summarizes recent diverse reactions employed in the formation of 1,3-polyols providing an overview of the mechanistic pathway and the enantioselectivity obtained, in terms of the properties of transition metals directly involved in the catalytic transformations and their interaction with various ligands.

Unified approach to fused and spirocyclic oxindoles through lewis-acid-promoted opening of spiroepoxyoxindoles with allylsilanes: application to the formal synthesis of (+/-)-physovenine - Sharma, Brijesh M.; Yadav, Mahesh; Gonnade, Rajesh G.; Kumar, Pradeep (European Journal of Organic Chemistry, 2017)
A protocol for the construction of oxindoles containing all-carbon quaternary centres in a highly regioselective manner has been developed. The reaction involves opening of spiroepoxyoxindoles with allylsilanes to give Hosomi-Sakurai-type products as well as new silicon-containing spirocyclic oxindoles. A formal synthesis of (+/-)-physovenine was accomplished in five steps using this protocol.
Keywords: alkaloids; Allylation; annulation; Lewis acids; spiro compounds

Harnessing nucleophilicity of allenol ester with p-quinone methides via gold catalysis: application to the synthesis of diarylmethine-substituted enones - Sharma, Brijesh M.; Rathod, Jayant; Gonnade, Rajesh G.; Kumar, Pradeep (Journal of Organic Chemistry, 2018)
A gold(I)-catalyzed protocol for intermolecular 1,6-conjugate addition of nucleophilic allenol ester generated in situ through [3,3]-sigmatropic rearrangement with p-quinone methides (p-QMs) has been developed. The gold catalyst plays a dual role by the pi-acid-triggered activation of alkynes and at the same time as a Lewis acid for activation of p-QMs toward nucleophilic attack. This method enables rapid access to a wide range of densely functionalized diarylmethine-substituted enones, a Morita-Baylis-Hillman (MBH) product with high selectivity, excellent yields, and broad substrate scope.

Proline-catalyzed asymmetric -amination in the synthesis of bioactive molecules - Kumar, Pradeep; Sharma, Brijesh M. (Synlett, 2018)
The direct -amination of carbonyl compounds using organocatalysts represents a powerful and atom-economical tool for asymmetric C-N bond formation. We describe a complete account of -functionalization of carbonyl compounds, through iterative sequential -aminoxylation/amination using electrophilic O and N sources, as well as sequential -amination/HWE reaction for enantio- and diastereoselective synthesis of both syn - and anti -1,3-aminoalcohols and 1,3-diamines. Additionally this protocol is further extended for the easy construction of alkaloids such as indolizidine, pyrrolizidine, and quinolizidine fused-ring systems just by tuning the chain length of the aldehyde used as a starting material. This methodology provides further scope to extrapolate it for a variety of naturally occurring hydroxylated monocyclic and fused bicyclic pyrrolidine and piperidine based alkaloids such as lentiginosine, epi -lentiginosine, dihydroxypyrrolizidine, (+)-deoxoprosophylline and (-)-deoxoprosopinine alkaloids. Furthermore, we have also uncovered proline-catalyzed anti -selectivity for the synthesis of 1,2-amino alcohols in -amination of aldehyde and one-pot indium-mediated Barbier type allylation of -hydrazino aldehydes to accomplish the total synthesis of clavaminols, sphinganine and spisulosine with reduced number of steps and with high overall yields. 1 Introduction 2 Application in the Total Synthesis of Alkaloids 3 Conclusion

Unravelling the nucleophilicity of buten tides for 1,6-conjugate addition to p-quinone methides: a direct access to diversely substituted butenolide-derived diarylmethanes - Sharma, Brijesh M.; Shinde, Dinesh R.; Jain, Ruchi; Begari, Eeshwaraiah; Satbhaiya, Shruti; Gonnade, Rajesh G.; Kumar, Pradeep (Organic Letters, 2018)
A Lewis acid catalyzed regioselective C-C bond is constructed through beta-addition of deconjugated butenolides with p-quinone methides in a 1,6-conjugate addition manner. Interestingly, Lewis acid catalyzed vinylogous Mukaiyama-Michael reaction of silyloxyfurans with p-QMs proceeds selectively through the alpha or gamma position exclusively. The reaction is mild with broad substrate scope, thus allowing easy access to a wide range of bis-arylated alpha-/beta-/gamma-substituted butenolides.

Continuous flow solvent free organic synthesis involving solids (reactants/products) using a screw reactor - Sharma, Brijesh M.; Atapalkar, Ranjit S.; Kulkarni, Amol A. (Green Chemistry, 2019)
Here we report for the first-time various organic transformations such as aldol condensation, oxidation, nucleophilic substitutions, protection, acylations and coupling reactions using a mechanochemical approach at a controlled temperature using a single synthesis platform. Almost minimal solvents or solvent-free conditions are used, making it a very efficient and clean synthesis of various products. A jacketed screw reactor when operated at different temperatures (0 degrees C to 160 degrees C) and over a range of rotation speeds for changing the residence time (15 s-300 s) helped to achieve maximum conversion. This approach is also extended to the synthesis using substrates having different substitutions, heterocycles and steric hindrance.